IMPLEMENTASI TEKNIK MENGHARDIK PADA KLIEN DENGAN HALUSINASI PENDENGARAN DI RUMAH SAKIT Dr. RADJIMAN WEDIODININGRAT : Implementation of Rebuked Techniques in Clients with Hearing Hallucinations at the Hospital Dr. Radjiman Wediodiningrat - Anam, Adib Khoirul; Zaini, Mad (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Auditory hallucinations are an individual mental disorder characterized by changes in sensory perception. Sufferers actually experience sensory distortion and feel false sensations in the form of sounds that the client actually feels do not exist. Hallucinations can be prevented by teaching clients to control hallucinations by implementing implementation strategies by rebuking hallucinations. Aim of this case study is to prevent hallucinations through implementing the Rebuke Technique at the Dr. Radjiman Wediodiningrat Hospital. Method used is a descriptive case study in the form of an in-depth case study on hallucinating clients by means of interviews, observation, physical examination, documentation studies, and providing nursing care to hallucinating clients by implementing the implementation of the Rebuke Technique. The Rebuke Technique nursing care was implemented for 15 minutes, carried out from April 16 to April 18, 2024. Evaluation was carried out on the third day. The results show that before being given nursing care to hallucinating clients through the Rebuke Technique, the client was unable to control the hallucinations, and after being given the implementation of the rebuke technique, the client was able to control the hallucinations. Implementation of the rebuke technique can control hallucinations after treatment for 3x24 hours. Advice as a family is to understand the prevention of hallucinations using the Rebuke Technique so that you can make efforts to deal with hallucinations at home.